Pengaruh Peranan Sistem Informasi dan Kinerja Pemasaran terhadap Keunggulan Bersaing Berkelanjutan pada Pengusaha Kerajinan Bambu di Kabupaten Jember - Supriyadi Supriyadi (Jurnal Aplikasi Manajemen, 2010)
Agroindustry as one of agribusiness system sub has important role in movement of national economy activity. Besides, role of agroindustry especially having location in rural is to increase industry earnings. as well as increasing quality than it self agricultural produce. This research is aim (1) to analyze and test Information System Role influence to revenues marketing performance on industry brass company Bamboo Handycaraf in Jember Regency. (2) lo analyze and test Information System Role influence torevenues Sustainable Competitive Advantage on industry brass company Bamboo Handycaraf in Jember Regency. (3) to analyze and test Marketing Performance influence to revenues Sustainable Competitive Advantage on industry brass company Bamboo Handycaraf in Jember Regency. Method applied in this research is survey research by using questionnaire as a means of data colleting. Research subject is the lead of industry brass company. Simultaneously testing by using Path Analyze. Obtained that selling Creativity, innovation, Markeung Performance. This research will be to give an answer difference this research.